Comparing the 1997 update of the 1982 American College of Rheumatology (ACR-97) and the 2012 Systemic Lupus International Collaborating Clinics (SLICC-12) criteria for systemic lupus erythematosus (SLE) classification: which enables earlier classification of SLE in an urban Asian population? - Low, E S H; Krishnaswamy, G; Thumboo, J (Lupus, 2019)
Objective We compared the 1997 update of the 1982 American College of Rheumatology (ACR-97) and the 2012 Systemic Lupus International Collaborating Clinics (SLICC-12) criteria, for earlier classification of systemic lupus erythematosus (SLE) in a multiethnic urban Asian SLE population. Methods Patients from a retrospective, nested case-control study of the influence of lupus nephritis on mortality in SLE were studied. For each patient, dates of first manifestations of each criteria (both ACR-97 and SLICC-12) were recorded, and the date of disease classification using ACR-97 or SLICC-12 criteria was compared to determine which criteria resulted in earlier classification. Results Among 182 SLE patients (74.2% Chinese, 18.1% Malay, 4.4% Indian and 3.3% Other ethnicities), 10 (5.5%) did not fulfill the ACR-97 criteria and 2 (1.1%) did not fulfill the SLICC-12 criteria. Using the SLICC-12 criteria, 18% of subjects showed earlier classification, whereas 7% of subjects showed earlier classification using the ACR-97 criteria. The SLICC hematologic criteria of “Leukopenia or lymphopenia” contributed most significantly to earlier diagnosis by SLICC-12. “Leukopenia or lymphopenia'' was present in 59% (19/32) of patients where SLICC-12 criteria allowed for earlier classification than ACR-97, compared with 15.4% (2/13) of patients where ACR-97 allowed earlier classification than SLICC-12 (p = 0.02). The immunologic criterion that is considered a strength of the SLICC-12 criteria did not appear to contribute significantly to earlier diagnosis in this study. Conclusion SLICC-12 criteria allow for earlier classification of SLE in a multiethnic cohort of Asian patients, supporting the validity of the SLICC-12 criteria and its use in clinical care and research.